The regional role of Turkey and Iran in the current Arabe situation - hathout, noureddin; mimouni, salima (Journal of Social Sciences and Humanities, 2021)
The foreign policy of a State reflects developed permanent interests in accordance with intertwined internal and external parameters within its role at the regional and international systems, in which; it seeks a distinctive role in accordance with the directions of the external decision-makers. The international environment over the latest decades has been an important base of study of foreign policy in the current international system, amid the escalating regional polarization and conflicts of a new nature, with variables of the assumptions underlying traditional foreign policy that have not been entirely sound about strategic spaces of influence. Iran and Turkey are trying to exploit historical conditions in the Middle East region that allow for expansionist ambitions. This study monitors the most important changes in the regional environment and their implications for the two States.